Animal Imagery in the Satanism of Anton LaVey. (12th April 2021) - Andrade, Gabriel
Abstract: The Church of Satan has used animal tropes recurrently. This article analyzes some of the most important animal representations that Anton LaVey came up with, both for esthetic and ideological purposes. Seizing on the long traditions of Satanism, LaVey embraced goat imagery to a significant degree. He also chose this particular animal for its associations with Pan, and the themes surrounding sexuality. Likewise, he embraced the snake, lion, and panthers. Yet, his choice of animal symbolism went beyond the esthetic. As he established the Church of Satan, LaVey hoped to construct an ideology that would emphasize humans' animalistic aspect. In this endeavor, he also made use of animal imagery.